2018
DOI: 10.24321/0019.5138.201808
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase and NDM-1 Production by Escherichia coli and Klebsiella pneumoniae from Patients belonging to a Rural Community in North India Hospitalized with CommunityAcquired Infections

Abstract: Carbapenem-resistant Enterobacteriaceae, especially New Delhi metallo-β-lactamase type-1-producing strains, exhibit multidrug resistance, thus posing a serious public health threat for treatment of infections caused by Gram-negative bacteria. However, most of the studies on the problem have been confined to hospitalized patients from urban population. The present study was carried out to detect carbapenemase production among Escherichia coli and Klebsiella pneumoniae Isolated from rural population hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As opposed to this pharmacy outlet-based study that may not be representative of the problem in the general community, the present study on antibiotic usage was based on survey in two distinct subpopulations from urban and rural community. Considering the overall low literacy rate in the two study subpopulations to clearly recognise medications as antibiotics and non-availability of prescriptions, the present study relied on usage of drugs in ailments suggestive of bacterial infection as correlate of antibiotic usage which showed self-medication of probable While there are few reports on the intestinal carriage rate of ESBL mediated AMR among healthy rural community in India, ranging from 15.4% to 33.8% 25,26 , there is hardly any information available on carriage rate of carbapenem and NDM-1 mediated AMR in the healthy rural community, most of the reports originating from studies on hospitalized patients from rural community 14 . Laxminarayan and Choudhary reported that non-prescription sales of carbapenems in India is among the highest in the world contributing to growing problem of carbapenem resistance 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As opposed to this pharmacy outlet-based study that may not be representative of the problem in the general community, the present study on antibiotic usage was based on survey in two distinct subpopulations from urban and rural community. Considering the overall low literacy rate in the two study subpopulations to clearly recognise medications as antibiotics and non-availability of prescriptions, the present study relied on usage of drugs in ailments suggestive of bacterial infection as correlate of antibiotic usage which showed self-medication of probable While there are few reports on the intestinal carriage rate of ESBL mediated AMR among healthy rural community in India, ranging from 15.4% to 33.8% 25,26 , there is hardly any information available on carriage rate of carbapenem and NDM-1 mediated AMR in the healthy rural community, most of the reports originating from studies on hospitalized patients from rural community 14 . Laxminarayan and Choudhary reported that non-prescription sales of carbapenems in India is among the highest in the world contributing to growing problem of carbapenem resistance 27 .…”
Section: Discussionmentioning
confidence: 99%
“…PCR for detection of bla NDM was carried out for carbapenemase producing stains using the pre-published sequences viz. forward 5'-ACCGCCTGGACCGATGACCA-3' and reverse 5'-GCCAAAGTTGGGCGCGGTTG-3', which amplified 264 bp fragment of the bla NDM gene 14 . Gene sequencing of the amplicons was done for all the bla NDM genes with amplicons purified by PCR purification kit (QIAGEN, Hidden, Germany).…”
Section: Molecular Identification Of Bla Tem Bla Shv Bla Ctx-m and Bla Ndm Genesmentioning
confidence: 99%